Is global ocean sprawl a cause of jellyfish blooms?. Issue 2 (7th September 2012) - Duarte, Carlos M; Pitt, Kylie A; Lucas, Cathy H; Purcell, Jennifer E; Uye, Shin-ichi; Robinson, Kelly; Brotz, Lucas; Decker, Mary Beth; Sutherland, Kelly R; Malej, Alenka; Madin, Laurence; Mianzan, Hermes; et al.
Abstract : Jellyfish (Cnidaria, Scyphozoa) blooms appear to be increasing in both intensity and frequency in many coastal areas worldwide, due to multiple hypothesized anthropogenic stressors. Here, we propose that the proliferation of artificial structures – associated with (1) the exponential growth in shipping, aquaculture, and other coastal industries, and (2) coastal protection (collectively, "ocean sprawl") – provides habitat for jellyfish polyps and may be an important driver of the global increase in jellyfish blooms. However, the habitat of the benthic polyps that commonly result in coastal jellyfish blooms has remained elusive, limiting our understanding of the drivers of these blooms. Support for the hypothesized role of ocean sprawl in promoting jellyfish blooms is provided by observations and experimental evidence demonstrating that jellyfish larvae settle in large numbers on artificial structures in coastal waters and develop into dense concentrations of jellyfish‐producing polyps.